Pengaruh Kepemilikan Asing dan Kepemilikan Institusional terhadap Biaya Modal Ekuitas: Efisiensi Investasi sebagai Variabel Mediasi - Robert Jao; Paulus Tangke; Anthony Holly; Luis Glinka Vinsensius Rumagit (Journal of Financial and Tax, 2023)
This study aims to investigate the effect of foreign ownership and institutional ownership on the cost of equity capital with investment efficiency as a mediating variable. This research was built with agency theory. The research method used in this study is a quantitative method. The population used in this study are all non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2018-2020. This study uses secondary data in the form of financial reports and annual reports obtained from the Indonesia Stock Exchange and the company's official website. The number of samples as many as 130 companies for 3 years were selected using purposive sampling method. The results of this study found that foreign ownership and institutional ownership have a positive effect on the cost of equity capital. The results of this study also found that foreign ownership, institutional ownership, and investment efficiency have a negative effect on the cost of equity capital. Finally, the findings of this study are that investment efficiency mediates the effect of foreign ownership and institutional ownership on the cost of equity capital.